Innovative territorial cluster as center of formation of labor activity of the innovative person (Путеводитель предпринимателя)
The article is devoted to innovative regional cluster as a center of formation of innovative employment rights. The authors describe the current state of ICTand a number of necessary conditions for the successful implementation of cluster policy.